Strategic Environmental Assessment (SEA): An introductory episode for Forestry Sector in Nepal - Shrestha, Tej Kumar (The Initiation, 2014)
DOI: http://dx.doi.org/10.3126/init.v5i0.10264 The Initiation 2013 Vol.5; 143-146